Os trabalhos manuais no Annuario do Ensino do Estado de São Paulo e na Revista de Ensino da Associação Beneficente do Professorado Público de São Paulo: (1902-1920) - Santos, Tainã Maria Pinheiro dos (2012)
The establishment of the Republic in Brazil in 1889 was accompanied by promises of a new era of progress, reason, science and civilization. Education in the discourse of many Republicans, has been considered the main promoter of this new era, the formation of the new man . In contrast to the Education of the monarchic period, considered traditional , set out new knowledge, new methods, new school practices, including those who valued the work and manual training, which were proposed for the full development - physical intellectual and moral. This research aims to understand the proposals relating to elementary education, printed in: Revista de Ensino Beneficente do Professorado Público do Estado de São Paulo, and Annuario do Ensino do Estado de São Paulo, from 1902 until 1920, seeking to understand the discourse and the practices on these education proposals, the contradictions faced, ruptures and continuities, until its decline